Modification of coal-tar pitch for use as a precursor for matrix carbon in carbon-carbon composites - Sarah F. Myram (1999)
In this work a series of pitches was prepared from two binder pitches, A and B, by sparging with hydrogen- and oxygen-containing gases, for different time intervals. The pitches were then characterised in terms of a number of chemical and physical properties. A model was developed which was used in conjunction with the pitch properties to determine whether sparging had involved chemical processes. It was found that for pitch A, sparging with hydrogen- and oxygen-containing gases involved chemical changes but that these changes were independent of gas type. These chemical changes lead to an increase in toluene insoluble material. This material was unable to withstand pyrolysis and thus did not increase the carbon yield of the pitch. Since the reactions in pitch A were independent of gas type it was concluded that they were probably thermally induced. For pitch B it was found that chemical reactions occurred and this time they were dependant on the gas type. The reactions that occurred for pitch B in hydrogen were concluded to be the same as those that occurred in pitch A but the reactions taking place in pitch B treated with oxygen were different. These reactions lead to an enhanced amount of toluene insoluble material. This material was able to withstand pyrolysis and hence increased the carbon yield. This reaction was predicted to be either an oxidative molecular growth or a decrease in volatility of polyaromatics brought about by the addition of oxygen functionality. In the second stage of this work carbon composites were fabricated using the series of pitches as matrix precursors. The properties of the composites were obtained and examined to see if they correlated with the properties of the pitches used to make the composites. It was found that the composite characteristics correlated closely with their constituent pitch characteristics, especially in the fact that the characteristics of the composites made from pitches B treated with oxygen were markedly different from all the others. It was concluded that the characteristics that were notably different for pitches B treated with oxygen were a direct result of the different reactions that occurred in these pitches compared to the reactions that had occurred in the other pitches.